Prevention and Control of Fusarium spp., the Causal Agents of Onion (Allium cepa) Basal Rot - Ofir Degani; Elhanan Dimant; Asaf Gordani; Shaul Graph; Eliyahu Margalit (Horticulturae, 2022)
Fusarium basal rot disease (FBR) is considered a serious threat to commercial onion production in Israel and worldwide. Today, coping means applied in Israel against the disease have limited efficiency and include a four-year crop cycle and disinfecting the soil with metam sodium. At the same time, agricultural tools (harrows, plows, etc.), contaminated equipment and workers facilitate spread of the disease to new growth areas, and the field disease incidence in Israel now reaches 8% of yields in heavily infected areas. Infected onions do not always show disease symptoms and the problem worsens if they arrive at storage facilities, especially since this pathogen genus produces known toxins. The current study aims at examining the potential of chemical control to reduce the damage caused by this disease. To this end, nine commercial fungicides were scanned in plate sensitivity assay against the main pathogens involved, Fusarium oxysporum f. sp. cepae and Fusarium acutatum. Several fungicides were found to be highly effective against the two pathogens, especially the mixtures Azoxystrobin + Difenoconazole, Fluopyram + Trifloxystrobin, or the Fluazinam compounds. Three selected preparations previously tested in seedlings were evaluated here in a full growing season. Prochloraz successfully protected the Orlando variety (white onion, Riverside cv.) and the Noam variety (red onion) at all growth stages against F. oxysporum f. sp. cepae. At the same time, this treatment was ineffective against F. acutatum in Noam cv. Another anti-fungal preparation, Fludioxonil + Sedaxen mixture, showed a wider range of effectiveness at the season’s end against the two Fusarium species tested in both onion cultivars. These results are an important step towards developing FBR control in commercial onion fields. Follow-up work is needed to optimize the pesticides’ concentrations and their application methods and to test them on a field scale. Interestingly, these pathogens were more aggressive towards the cultivar from which they were isolated: F. oxysporum f. sp. cepae to the red onion Noam cv. and F. acutatum to the white Orlando cv. Infecting the plants with both pathogens reduced disease symptoms in the white Orlando cv, suggesting antagonistic interactions in this onion genotype.